(untitled) (Psychology Travelogs, 2024)
The article presents the results of an empirical study of the levels of anxiety of adolescents during the war. Such methods were used: the test "Scale of Reactive (Situational) and Personal Anxiety" by Spielberger - Khanin; Questionnaire "Anxiety Scale" by J. Taylor, adaptation by M. M. Peisakhov; "Scale of Social and Situational Anxiety" by O. Kondash; Beck’s Anxiety Scale; author’s questionnaire for identifying anxiety of adolescents during the war (A. Fedosyuk). In the study 61 people - students of grades 7-8 of secondary school – took part. It was revealed the level of situational, personal, school, interpersonal and self-esteem anxiety of adolescents. The largest part of the respondents has an average level of anxiety, which is natural for adolescence. The high level of anxiety found in some adolescents indicates their emotional vulnerability and need for psychological support. Some of the subjects have a low level of anxiety, which may indicate their adaptability and stress resistance. It was shown, that such war factors as sound of air alarm, explosions and media content influence the most on the adolescents’ anxiety. The general impact of war on the physical and mental well-being of adolescents, their relationships with their loved was analyzed. It was shown that war negatively affects adolescents. War conditions contribute to an increase in the level of anxiety in adolescents, which is manifested in situational, personal, school, interpersonal and self-esteem anxiety. Many adolescents experience a deterioration in their emotional state, difficulties with concentration and a decrease in motivation to study. Prospects for further research: to develop the corrective programs and recommendations to help adolescents overcome anxiety states and adapt to crisis conditions.